2021
DOI: 10.1182/blood.2020010510
|View full text |Cite
|
Sign up to set email alerts
|

14q32 rearrangements deregulating BCL11B mark a distinct subgroup of T and myeloid immature acute leukemia

Abstract: Acute leukemias (AL) of ambiguous lineage are a heterogeneous group of high-risk leukemias characterized by co-expression of myeloid and lymphoid markers. In this study, we identified a distinct subgroup of immature acute leukemias characterized by a broadly variable phenotype, covering acute myeloid leukemia (AML M0 or M1), T/myeloid mixed phenotype acute leukemia (T/M MPAL), and early T-cell precursor acute lymphoblastic leukemia (ETP-ALL). Rearrangements at 14q32/BCL11B are the cytogenetic hallmark of this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(47 citation statements)
references
References 50 publications
3
44
0
Order By: Relevance
“…Dysregulated expression of HOX transcription factor genes is mostly induced by chromosomal translocations and inversions that juxtapose these genes to enhancers in the TCR and BCL11B regulatory regions [135,146]. Importantly, BCL11B rearrangements (BCL11B-TLX3) in this subgroup are mechanistically distinct from those identified in BCL11B-rearranged lineage ambiguous leukemias, in that in the BCL11B-TLX3 leukemia, the BCL11B enhancer is used for aberrant expression of TLX3 at the cost of the loss of expression of BCL11B, leading to complete difference in expression profiles [5,146,147]. Instead, TLX3 rearranged T-ALL (including BCL11B-TLX3) shares gene expression signatures, DNA methylation profiles, somatic mutations (BCL11B, WT1, PHF6, DNM2), and downstream targets (JAK-STAT, epigenetic regulators) with TLX1 rearranged T-ALL [135,136,142,143,145].…”
Section: T-all In Early Stages Of Cortical Thymocyte Maturationmentioning
confidence: 99%
See 1 more Smart Citation
“…Dysregulated expression of HOX transcription factor genes is mostly induced by chromosomal translocations and inversions that juxtapose these genes to enhancers in the TCR and BCL11B regulatory regions [135,146]. Importantly, BCL11B rearrangements (BCL11B-TLX3) in this subgroup are mechanistically distinct from those identified in BCL11B-rearranged lineage ambiguous leukemias, in that in the BCL11B-TLX3 leukemia, the BCL11B enhancer is used for aberrant expression of TLX3 at the cost of the loss of expression of BCL11B, leading to complete difference in expression profiles [5,146,147]. Instead, TLX3 rearranged T-ALL (including BCL11B-TLX3) shares gene expression signatures, DNA methylation profiles, somatic mutations (BCL11B, WT1, PHF6, DNM2), and downstream targets (JAK-STAT, epigenetic regulators) with TLX1 rearranged T-ALL [135,136,142,143,145].…”
Section: T-all In Early Stages Of Cortical Thymocyte Maturationmentioning
confidence: 99%
“…Consistent with this, recent studies have defined a subgroup of BCL11B-deregulated ALAL, that includes one third of ETP-ALL and T/myeloid mixed phenotype acute leukemia (T/M MPAL) cases with a very distinct expression profile [5]. BCL11B-deregulated ALAL is characterized by structural variations of the region containing BCL11B at 14q32 including translocations and high-copy amplification generating a distal neo-enhancer, that each leads to aberrant expression of BCL11B, in the case of the rearrangements by hijacking super-enhancers active in CD34+ hematopoietic stem and progenitor cell (HSPCs) [5,147]. FLT3 activating mutations were found in 80% of BCL11B-deregulated ALAL, and concurrent expression of BCL11B and FLT3-ITD on HSPC exhibited synergistic effects on activating T-cell directed differentiation to express cytoplasmic CD3 while blocking myeloid differentiation [5].…”
Section: Early T-cell Precursor (Etp) All and Mixed Phenotype Acute Leukemiamentioning
confidence: 99%
“…A new leukemia subtype (BCL11B-a), with a variable phenotype, characterized by coexpression of myeloid and T-lymphoid markers, and ranging from ETP-ALL to immature AML, has been recently identified by our group in adults and by Montefiori LE et al in children [10,43]. This immature form of leukemia is driven by transcriptional activation of BCL11B, due to chromosomal rearrangements that juxtapose BCL11B to diverse, active super-enhancers, or to the ZEB2 gene, generating a ZEB2-BCL11B fusion.…”
Section: The Bcl11b-a Entitymentioning
confidence: 97%
“…Furthermore, BCL11B-a AL have a distinct expression profile, characterized by deregulation of BCL11B target genes, inhibition of the T-cell differentiation program, and activation of the JAK/STAT. As predicted by the genomic profile, BCL11B-a AL cases are sensitive to tyrosine kinase and JAK/STAT inhibitors, i.e., NVP-BVB808, Momelotinib, Fedratinib, and NVP-BSK805 [10]…”
Section: The Bcl11b-a Entitymentioning
confidence: 99%
“…Recently, a study on acute leukemias of ambiguous lineage showed the recurrence of 14q32 rearrangements resulting in the activation of BCL11B , co-occurring with FLT3 , DNMT3A , TET2 and WT1 variants. GEP identified a specific expression signature related to BCL11B activation with significant downregulation of its targets, providing a novel biomarker for a new entity among immature acute leukemias [ 29 ].…”
Section: Introductionmentioning
confidence: 99%